Peran Kepala Madrasah dalam Mengimplementasikan Manajemen Berbasis Sekolah: Studi Kasus di Madrasah Aliyah Al Azhar Modung Bangkalan - Rizkillah Adi Candra; Ahmad Ali Riyadi; Irmawan Jauhari (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
The implementation of school-based management, the madrasah head is a driving actor, determines the direction of madrasah policy, which will determine how the objectives of madrasah and education in general are realized. This study aims to: (1) To find out the planning process of madrasah principals in the implementation of MBS at Madrasah Aliyah Al Azhar Modung Bangkalan, (2) To find out the role of madrasah principals as educators in school-based management at Madrasah Aliyah Al Azhar Modung Bangkalan, (3) To find out the role of madrasah principals as supervisors in school-based management at Madrasah Aliyah Al Azhar Modung Bangkalan. This type of research includes field research, using qualitative methods using a descriptive approach. While collecting data through interviews, observation and documentation. The research findings show that: (1) The Planning Process for the Implementation of Madrasah Based Management of Madrasah Aliyah Al Azhar Modung Bangkalan runs quite well and is carried out by involving the committee (student guardians, community leaders and donors) and all other madrasah components. (2) The head of Madrasah Aliyah Al Azhar Modung Bangkalan in implementing MBS as an educator must have the ability to guide teachers, non-teaching staff, students, develop educational staff, science and technology and provide teaching examples. (3) The head of Madrasah Aliyah Al Azhar Modung Bangkalan in implementing MBS as a supervisor must provide guidance, assistance, supervision, assessment on the technical implementation and development of education, teaching, program improvement, teaching activities. And must have the ability to compile, implement clinical, non-clinical, extra-curricular supervision programs.